2015
DOI: 10.1523/jneurosci.3973-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Neuropeptides on Excitatory Synaptic Transmission in Human Epileptic Hippocampus

Abstract: Development of novel disease-modifying treatment strategies for neurological disorders, which at present have no cure, represents a major challenge for today's neurology. Translation of findings from animal models to humans represents an unresolved gap in most of the preclinical studies. Gene therapy is an evolving innovative approach that may prove useful for clinical applications. In animal models of temporal lobe epilepsy (TLE), gene therapy treatments based on viral vectors encoding NPY or galanin have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 44 publications
(4 reference statements)
2
45
0
Order By: Relevance
“…), but neuropeptide Y was shown to suppress abnormal excitatory currents in human epileptic tissue (Ledri et al . ). In addition, disruption of adenosine and D‐serine signaling mechanisms associates with post‐synaptic molecular changes and lower seizure threshold (Klatte et al .…”
Section: Synapse Dysfunction In Neurodevelopmental Disordersmentioning
confidence: 97%
See 1 more Smart Citation
“…), but neuropeptide Y was shown to suppress abnormal excitatory currents in human epileptic tissue (Ledri et al . ). In addition, disruption of adenosine and D‐serine signaling mechanisms associates with post‐synaptic molecular changes and lower seizure threshold (Klatte et al .…”
Section: Synapse Dysfunction In Neurodevelopmental Disordersmentioning
confidence: 97%
“…Indeed, neuropeptides and small molecule coagonists known to regulate network excitability and transmission tonus have been investigated for their potential to enhance seizure threshold, and gene therapy has been proposed as a treatment approach (Riban et al 2009). Among neuropeptides, brain-derived neurotrophic factor appears to promote epileptogenesis via TrkB activation (Liu et al 2013;Gu et al 2015), but neuropeptide Y was shown to suppress abnormal excitatory currents in human epileptic tissue (Ledri et al 2015). In addition, disruption of adenosine and D-serine signaling mechanisms associates with post-synaptic molecular changes and lower seizure threshold (Klatte et al 2013;Boison 2016).…”
Section: Epilepsymentioning
confidence: 99%
“…Importantly, resected brain tissue taken from epileptic patients has provided evidence that NPY reduces excitatory transmission in the dentate gyrus and region CA1, via Y2 receptors, also in the human brain (Ledri et al, 2015;Patrylo et al, 1999). Furthermore, expression of NPY as well as Y1 and Y2 receptors undergo considerable plastic changes in the dentate gyrus and subiculum in animal models of epilepsy and in human tissue obtained by temporal lobe epilepsy surgery (Furtinger et al, 2001;Vezzani and Sperk, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Of particular interest has been neuropeptide Y (NPY), which is widely and abundantly expressed in the mammalian central nervous system (CNS) and is a member of the pancreatic polypeptide family with 3 subtypes: Y1, Y2 and Y5. NPY is co‐localized with several other neurotransmitters and is a critical inhibitory regulator of neuronal excitability . A growing body of literature suggests that NPY plays an antiepileptic role in acquired focal epilepsy in patients as well as in animal models of acquired epilepsies…”
Section: Introductionmentioning
confidence: 99%
“…NPY is co-localized with several other neurotransmitters and is a critical inhibitory regulator of neuronal excitability. 5,6 A growing body of literature suggests that NPY plays an antiepileptic role in acquired focal epilepsy in patients 7,8 as well as in animal models of acquired epilepsies. 9,10 The seizures of GGEs, particularly absence seizures, involve pathologic oscillations of the cortico-thalamo-cortical circuit.…”
Section: Introductionmentioning
confidence: 99%